Design and Applications of High Force Generation in 3D-Printed Pneumatic Artificial Muscles - Jae Hyeong Park; Seungweon Jeon; Young Jin Gong; Jimin Yoon; Dongsu Shin; Hyeon-Woong Seo; Bo Geun Kim; Ja Choon Koo; Hyungpil Moon; Rodrigue Hugo; Hyouk Ryeol Choi (Actuators)
Increasing the force generation and scalability of soft pneumatic actuators poses significant challenges in robotics applications, especially where high load capacities and precise control are required. This paper presents UniBPAM, a novel, scalable soft pneumatic actuator optimized through 3D printing to enhance force generation. By analyzing design parameters, such as the number of sides, height, and origami factor, UniBPAM achieved a 21.48% increase in force generation. Scalable across diameters from 36 to 144 mm, the actuator demonstrated the ability to lift up to 57 kg with 84.9% strain at larger scales. Additionally, the BiBPAM variant enables bidirectional actuation in robotic joints via motion control, which is realized through PID systems, making it suitable for various robotic applications.